ACADEMIC DISCIPLINE "ELECTRONIC DOCUMENT AND DATA PROTECTION" AS PART OF THE FORMATION OF A PROFESSIONAL COMPUTERINFORMATION COMPETENCE OF MASTERS OF PUBLIC SERVICE (Journal of Information Technologies in Education (ITE), 2013)
The article is devoted to the formation of a professional computer-information competence of masters of public service. The structure and content filling levels of computer-information competence of masters, they justify the purpose, tasks and content of the discipline "Electronic document management and data protection".
Keywords: Masters of the public service; computer information competence; electronic document management; information protection